REALIDAD Y PERSPECTIVAS EN LA APLICACIÓN DE LAS NUEVAS TECNOLOGÍAS A LA HISTORIA DEL ARTE - Gil Pujante, Francisco Antonio (Imafronte, 1991)
The application. to History of Fine Arts, of the many new means daily offered by technique and technology reveals itself as a very exciting field, as it provides researchers with a great variety of utilities. Interactive multimedia configurations, data bases (with their attached problems, such as cataloguing, normalization, etc.) and data banks, understood as a set of one or more data bases, sofmare, hardware, and the consultation language you need for a proper operation to mention only a few options- are of major interest not only because of their future applications, but also from those already implemented.